Meningkatkan Kemampuan Mengenal Lambang Bilangan Melalui Model Pembelajaran STAD (Student Teams Achievement Division) pada Anak Usia 4-5 - Rumiati, Rumiati; Nur Handayani, Iys (Early Stage, 2025)
This study aims to improve the ability to recognize number symbols 1-10 through the STAD (Student Teams Achievement Division) cooperative learning model in children aged 4-5 years. The research method used is classroom action research (CAR). The subjects of the study were all children aged 4-5 years at the Waluyo Jati 04 PAUD Post. Data analysis used was observation and documentation sheets. This implementation was carried out in two cycles. Each cycle consists of three meetings, each meeting contains three stages, namely planning, action and observation and reflection. The results of the study showed that the STAD (Student Teams Achievement Division) cooperative learning model can improve children's ability to recognize number symbols 1-10 in children aged 4-5 years at the Waluyo Jati 04 Gumelem Kulon PAUD Post. This can be seen from the increase in pre-action results up to cycle II research. The pre-action results obtained an average percentage of children's ability to recognize number symbols 1-10 of 20.83%, in cycle I an average percentage of 64.20% was obtained, and in cycle II an average percentage of 84.11% was obtained. These results are in accordance with the success indicators set by the researcher, which is 75%. It is concluded that the ability to recognize number symbols 1-10 through the STAD (Student Teams Achievement Divisions) cooperative learning model for children aged 4-5 years at the Waluyo Jati 04 Gumelem Kulon PAUD Post has increased.